Recruitmen Strategy, Tranining Program, and Organizational Commitment on Sustainability of Human Resouce Manajemen Practies - Muhammad Syafri (Journal of Economics and Economic Education, 2025)
This study examines the role of recruitment strategies, training programs, and organizational commitment in fostering the sustainability of human resource management (HRM) practices. Drawing on Social Exchange Theory (SET) and the Resource-Based View (RBV), the research positions recruitment and training as critical HR practices that shape employee commitment and long-term organizational resilience. Recruitment strategies focusing on fairness, inclusivity, and value alignment are essential for attracting talent aligned with sustainability objectives, while training programs emphasizing continuous learning and career development contribute to workforce adaptability. Organizational commitment serves as a mediating force, transforming HR practices into sustainable outcomes by enhancing employee loyalty, engagement, and alignment with organizational values. The study contributes theoretically by extending sustainable HRM literature and practically by offering actionable strategies for organizations to align HR practices with broader sustainability goals. Limitations are acknowledged, and directions for future research are proposed to explore additional HR practices and contextual factors influencing HRM sustainability.